A MOF-derived screening type carbon sodium negative electrode material and its preparation method and application

Through heat treatment of MOF materials and nitrogen sources and two chemical vapor deposition techniques, screened carbon materials with rich microporous structures are constructed, solving the problems of low energy density and poor low temperature performance of hard carbon materials, and significantly improving sodium ion batteries energy density and cycle stability.

CN119059513BActive Publication Date: 2025-01-14NAKUN CARBON SOURCE (TIANJIN) TECHNOLOGY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411547895.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-14
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing hard carbon materials have low energy density and poor low-temperature cycling performance in sodium ion batteries. The porous carbon materials derived from traditional MOF have a wide pore size distribution and are all open-porous structures, so they cannot effectively screen sodium ions of specific sizes, resulting in sodium storage. Efficiency and cycle stability decrease.

Method used

Porous carbon materials are prepared by selecting MOF materials as precursors and combining nitrogen sources for heat treatment. They are constructed with two chemical vapor deposition processes to create a screened carbon material with rich microporous structures and adjustable pore sizes, which is applied to sodium ion batteries. middle.

Benefits of technology

A rich closed-cell structure and adjustable pore size carbon material have been achieved, which significantly improves the energy density and low-temperature performance of sodium ion batteries. The first reversible capacity reaches 419mAh/g, the first Coulomb efficiency is 89%, and the low-temperature capacity retention rate is 75%. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119059513B_ABST
    Figure CN119059513B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion batteries, and in particular to a MOF-derived screening type carbon sodium negative electrode material and a preparation method and application thereof. The preparation method comprises: preparation of a MOF-derived porous carbon material precursor and preparation of a screening type carbon negative electrode material, wherein the MOF-derived porous carbon material precursor is prepared by heat-treating and modifying a MOF material and a nitrogen source; the screening type carbon negative electrode material is prepared by chemical vapor deposition processes of the MOF-derived porous carbon material precursor twice at the same temperature and with different carbon source gases; the MOF-derived screening type carbon sodium negative electrode material has a rich closed-pore structure and the pore size of micropores in the closed-pore structure is adjustable, and is used in a sodium ion battery, with a first-cycle reversible capacity of 419 mAh / g, an initial coulombic efficiency of 89%, and a capacity retention rate of up to 75% at -30°C. Compared with the prior art, the technical problem that the prior art cannot have both a rich closed-pore structure and an adjustable pore size, resulting in poor energy density and poor low-temperature performance of the sodium ion battery, is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a MOF-derived screening-type carbon-sodium negative electrode material and a preparation method and application thereof. Background Art

[0002] With the transformation of the global energy structure and the growing demand for new energy technologies, sodium-ion batteries are considered to be a potential alternative to lithium-ion batteries due to their abundant resources, low cost, and superior low-temperature and fast-charging characteristics. Especially in large-scale energy storage systems and electric vehicle power systems, sodium-ion batteries have shown broad application prospects. As one of the core components of sodium-ion batteries, the negative electrode material directly affects the overall performance of the battery. Among them, hard carbon, as a negative electrode material for sodium-ion batteries, has attracted much attention due to its high specific capacity, more abundant sodium storage active sites, good stable cyclicity and excellent frequency doubling performance.

[0003] Due to their unique pore structure, hard carbon materials can provide a variety of sodium storage mechanisms, including embedded reactions, capacitive adsorption on the electrolyte surface, and sodium storage in the form of atomic clusters in closed pores. However, the pore structure of traditional hard carbon materials is usually relatively random, and the proportion of micropores is low, which limits their practical application to low energy density and poor low-temperature cycle stability. At present, the main research direction for improving the sodium storage performance of hard carbon materials is focused on optimizing their pore structure, especially the design of closed-pore structure. At low potential, sodium ions can form clusters in the closed-pore structure, contributing a large proportion of platform capacity. At the same time, under low temperature conditions, ion diffusion and electrochemical reaction rates are greatly reduced, resulting in the deterioration of battery capacity and cycle stability. Studies have shown that the rich microporous structure constructs more active sites for sodium ion reactions, which is more conducive to increasing the affinity of carbon materials for sodium ions, clustering reactions, and improving reaction kinetics. Therefore, as the micropore content of carbon materials increases, the material can exhibit better low-temperature performance. Therefore, constructing a carbon negative electrode material with a rich closed-pore structure and adjustable micropore diameter in the closed-pore structure is the key to improving the energy density of sodium-ion batteries and improving low-temperature performance. Existing methods for constructing hard carbon materials with closed-pore structures include direct carbonization, introduction of pore-forming agents, and template methods. Although these technologies can improve the sodium storage capacity to a certain extent, there are generally problems such as insufficient number of closed pores or unadjustable pore diameters and low proportion of micropores. It is often difficult to achieve the goals of rich closed-pore structure and adjustable pore diameter at the same time, which limits the performance of hard carbon materials in practical applications.

[0004] Metal-organic framework (MOF) is a porous inorganic-organic hybrid material. Due to its unique structural characteristics, high specific surface area and porosity, controllable crystal structure and adjustable pore size, it has attracted widespread attention in the field of energy storage, especially as an electrode material for secondary batteries such as lithium-ion batteries and sodium-ion batteries, showing excellent performance. At present, MOF-derived carbon materials are mainly obtained by pyrolysis of MOFs precursors. These carbon materials usually have a high specific surface area and rich pore structure, which is conducive to improving the sodium storage capacity of electrode materials. However, MOF porous carbon materials prepared by traditional methods often have a wide pore size distribution and are all open-pore structures. They cannot effectively screen sodium ions of a specific size, resulting in a decrease in sodium storage efficiency and cycle stability. At the same time, the thermal stability is poor, and the direct use of chemical vapor deposition will cause the pore structure to collapse. Some researchers have tried to improve the performance of carbon materials by doping other elements or introducing nanostructures, but these methods are often complex and costly, which is not conducive to large-scale production and application. Summary of the invention

[0005] In order to solve the problems of low energy density and poor low-temperature cycle performance of hard carbon negative electrodes in the prior art, the present invention provides a MOF-derived screening-type carbon-sodium negative electrode material and a preparation method and application thereof. A porous carbon material is prepared by selecting MOF material as a precursor, and then it is prepared into screening-type carbon through a CVD process to construct a hard carbon negative electrode material with rich microporous structure and adjustable pore size, which is applied to sodium ion batteries and has significant effects.

[0006] The present invention provides a MOF-derived screening type carbon sodium negative electrode material, including the preparation of a MOF-derived porous carbon material precursor and the preparation of a screening type carbon negative electrode material, wherein the MOF-derived porous carbon material precursor is prepared by modifying a MOF material and a nitrogen source through heat treatment, wherein the doping mass ratio of the MOF material to the nitrogen source is 1:0.3-1:2, and the temperature of the heat treatment is 600-800°C; the screening type carbon negative electrode material is prepared by subjecting the MOF-derived porous carbon material precursor to two chemical vapor deposition processes with the same deposition temperature and different carbon source gases, wherein the deposition temperature of the chemical vapor deposition is 700-900°C.

[0007] Furthermore, the carbon source gas includes aromatic hydrocarbon vapor and C1-C3 hydrocarbons, the aromatic hydrocarbon vapor is the carbon source gas in the first chemical vapor deposition process, and the ventilation rate is 5-300 ml / min; the C1-C3 hydrocarbons are the carbon source gas in the second chemical vapor deposition process, and the ventilation rate is ≥10 ml / min.

[0008] Preferably, the aromatic hydrocarbon vapor is benzene, toluene or xylene.

[0009] Preferably, the C1-C3 hydrocarbon is methane, ethane, acetylene or propane.

[0010] Furthermore, the MOF material is ZIF-8, ZIF-5 or ZIF-7, preferably ZIF-8.

[0011] Furthermore, the nitrogen source is urea, melamine, glutamine, pyridine or pyrrole, preferably urea or melamine.

[0012] Further, the method specifically includes the following steps:

[0013] (1) Soaking the MOF material and the nitrogen source in deionized water or anhydrous ethanol in proportion and stirring, stirring for 12 hours and then drying to obtain a mixed solid; placing the mixed solid in a tubular furnace, passing a protective gas, and performing heat treatment to obtain a carbonized cracking product after heat treatment for 2-4 hours;

[0014] (2) The carbonized pyrolysis product was stirred in 5% HCl for 12 h until no bubbles were generated in the solution and the pH was acidic, and then washed with deionized water until the pH of the solution was neutral and then dried to obtain a MOF-derived porous carbon material precursor;

[0015] (3) placing the MOF-derived porous carbon material precursor in a chemical vapor deposition device for chemical vapor deposition, first introducing a protective gas, heating to the deposition temperature, introducing aromatic hydrocarbon vapor, and performing the first heat preservation. After the heat preservation lasts for 10-30 minutes, the first chemical vapor deposition is completed;

[0016] (4) After the first chemical vapor deposition is completed, switch the carbon source gas, introduce C1-C3 hydrocarbons, and perform a second heat preservation, the heat preservation time is ≥3h, and the second chemical vapor deposition is completed;

[0017] (5) After completing two chemical vapor deposition phases, turn off the carbon source gas, keep the protective gas flowing, and cool down to room temperature at a cooling rate of 2-10°C / min to obtain a MOF-derived screening-type carbon sodium negative electrode material;

[0018] The amounts of HCl and deionized water used are both excessive, that is, the addition of HCl is stopped when no bubbles are generated and the pH is acidic, and the addition of deionized water is stopped when the pH of the solution is neutral.

[0019] Furthermore, the protective gases in steps (1) to (5) are all nitrogen or argon.

[0020] Furthermore, the specific surface area of ​​the MOF-derived porous carbon material precursor obtained in step (2) is 1300-1700 m 2 / g, preferably 1615m2 / g, 1501m 2 / g, 1443m 2 / g;

[0021] Furthermore, the average pore size of the MOF-derived porous carbon material precursor obtained in step (2) is in the range of 0.5-2.1 nm, preferably 0.8-1.6 nm;

[0022] Furthermore, the MOF-derived porous carbon material precursor obtained in step (2) has a micropore ratio of 70-80%, preferably 79.6%.

[0023] Furthermore, the total pore volume of the MOF-derived porous carbon material precursor obtained in step (2) is 0.46-0.5 cm 3 / g, preferably 0.497cm 3 / g.

[0024] Based on the above preparation method, the present invention provides a MOF-derived screening-type carbon sodium negative electrode material.

[0025] Preferably, the specific surface area of ​​the MOF-derived sieve-type carbon sodium negative electrode material is less than 10 m 2 / g.

[0026] The present invention also provides an application of the MOF-derived screening-type carbon-sodium negative electrode material in a sodium ion battery.

[0027] The advantages of the present invention are:

[0028] 1. The MOF-derived sieving-type carbon sodium negative electrode material obtained by the present invention through two chemical vapor deposition processes of a MOF-derived porous carbon material precursor has a rich and pore-adjustable closed-pore structure, a first-cycle reversible capacity of 419 mAh / g, an initial coulombic efficiency of 89%, and a capacity retention rate of 75% at low temperatures. Compared with the prior art, the present invention solves the technical problems that the prior art generally has insufficient number of closed pores or unadjustable micropore diameters, and cannot achieve both rich closed-pore structure and adjustable pore diameter, resulting in poor energy density of sodium ion batteries and poor cycle stability at low temperatures;

[0029] 2. The present invention prepares a unique MOF-derived porous carbon material precursor by introducing a certain amount of nitrogen source into the MOF material for nitrogen-doping modification, and its rich pore structure is retained, the pore volume is slightly reduced, while the specific surface area is greatly increased and the proportion of micropores is increased, which significantly improves the negative electrode rate performance and cycle stability;

[0030] 3. The carbon source gases used in the two chemical vapor deposition methods of the present invention are different. Under specific carbon source gases and processing conditions, the pores are rapidly reduced while ensuring their specific surface area, thereby improving the initial coulomb efficiency and sodium storage capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is the first cycle charge and discharge curve of the sodium ion battery negative electrode material of Example 1 of the present invention;

[0032] Figure 2 : is a nitrogen adsorption-desorption isotherm diagram of the MOF-derived porous carbon material before CVD and the screening-type carbon negative electrode material after CVD in Example 1 of the present invention;

[0033] Figure 3 is a pore size distribution diagram of the MOF-derived porous carbon material of Example 1 of the present invention;

[0034] Figure 4 This is the first cycle charge and discharge curve of the negative electrode material of Comparative Example 1 of the present invention;

[0035] Figure 5 It is the nitrogen adsorption-desorption isotherm of the porous carbon material precursor before CVD and the negative electrode material after CVD in Comparative Example 1 of the present invention;

[0036] Figure 6 is a pore size distribution diagram of the MOF-derived porous carbon material of Comparative Example 1 of the present invention;

[0037] Figure 7 It is a graph of low temperature capacity retention rates of Example 1 and Comparative Examples 1 and 8 of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the invention to clearly and completely describe the technical solutions in the embodiments of the invention. Obviously, the described embodiments are only part of the embodiments of the invention, not all of them. Based on the embodiments in the invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the invention.

[0039] It should be noted that the various installation methods and technical terms mentioned in the invention are technical terms that have long been clearly known in the relevant technical field, so no further explanation is given. In addition, the same reference numerals are used for the same components, but this does not affect and should not constitute an accurate understanding of the technical solution by those skilled in the art.

[0040] Example 1 This example is a MOF-derived screening-type carbon-sodium negative electrode material, the MOF material used is ZIF-8, the nitrogen source used is urea, the mass ratio of MOF material to urea is 1:1.3, the carbon source gas used for the first vapor deposition is xylene, and the carbon source gas used for the second vapor deposition is methane.

[0041] The preparation method of the MOF-derived screening-type carbon sodium negative electrode material of this embodiment comprises the following steps:

[0042] (1) ZIF-8 and urea were immersed in deionized water at a mass fraction ratio of 1:1.3 and stirred for 12 h, followed by drying to obtain a mixed solid; the mixed solid was placed in a tubular furnace, argon was introduced, and heat-treated at 800 °C to obtain a carbonized cracking product after heat treatment for 3 h;

[0043] (2) The carbonized pyrolysis product was stirred in an excess of 5% HCl for 12 h until the solution had no bubbles and the pH was acidic, and then washed with excess deionized water until the pH of the solution was neutral, and then dried to obtain a MOF-derived porous carbon material precursor;

[0044] (3) The MOF-derived porous carbon material precursor was placed in a chemical vapor deposition device and argon gas was introduced. After the temperature was raised to 750°C, xylene was introduced as a carbon source gas at a ventilation rate of 100 ml / min and the first heat preservation was performed. After 20 minutes of heat preservation, the first chemical vapor deposition was completed;

[0045] (4) After the first chemical vapor deposition, switch the carbon source gas to methane at a ventilation rate of 10 ml / min as the carbon source gas, and perform a second heat preservation for 4 hours to complete the second chemical vapor deposition;

[0046] (5) After completing two chemical vapor deposition phases, the carbon source gas was turned off, the argon gas was kept flowing, and the temperature was cooled to room temperature at a cooling rate of 10°C / min to obtain a MOF-derived screening-type carbon sodium negative electrode material.

[0047] Example 2 The nitrogen source and preparation method of a MOF-derived screening-type carbon sodium negative electrode material in this example are the same as those in Example 1, except that the parameter conditions involved in the preparation process are different (see Table 1 for details):

[0048] In the carbonization and cracking process of step (1), the mass ratio of ZIF-8 to urea is 1:0.3, the protective gas is argon, the heat treatment temperature is 800°C, and the heat treatment time is 2h;

[0049] In the first chemical vapor deposition process of step (3), the protective gas used is argon, the carbon source gas is benzene, the ventilation rate is 100 ml / min, the heating temperature is 900° C., and the holding time is 10 min;

[0050] During the second chemical vapor deposition process in step (4), the carbon source gas is switched to ethane, the ventilation rate is 10 ml / min, and the holding time is 3 h;

[0051] In step (5), the cooling rate is 2°C / min.

[0052] Example 3 The nitrogen source and preparation method of a MOF-derived screening-type carbon sodium negative electrode material in this example are the same as those in Example 1, except that the parameter conditions involved in the preparation process are different (see Table 1 for details):

[0053] In the carbonization and cracking process of step (1), the mass ratio of ZIF-8 to urea is 1:2, the protective gas is nitrogen, the heat treatment temperature is 600°C, and the heat treatment time is 4 hours;

[0054] In the first chemical vapor deposition process of step (3), the protective gas used is nitrogen, the carbon source gas is toluene, the ventilation rate is 50 ml / min, the heating temperature is 700°C, and the holding time is 30 min;

[0055] During the second chemical vapor deposition process in step (4), the carbon source gas was switched to propane, the ventilation rate was 10 ml / min, and the holding time was 4 h.

[0056] Example 4 The preparation method of a MOF-derived screening-type carbon sodium negative electrode material in this example is the same as that in Example 1, except that the nitrogen source used and the parameter conditions involved in the preparation process are different (see Table 1 for details):

[0057] The nitrogen source used in this embodiment is melamine;

[0058] In the carbonization and cracking process of step (1), the mass ratio of ZIF-8 to melamine used is 1:1.3, the protective gas is argon, the heat treatment temperature is 800°C, and the heat treatment time is 3h;

[0059] In the first chemical vapor deposition process of step (3), the protective gas used is argon, the carbon source gas is xylene, the ventilation rate is 300 ml / min, the heating temperature is 750°C, and the holding time is 20 min;

[0060] During the second chemical vapor deposition process in step (4), the carbon source gas was switched to methane, the ventilation rate was 15 ml / min, and the holding time was 4 h.

[0061] Example 5 The nitrogen source and preparation method of a MOF-derived screening-type carbon sodium negative electrode material in this example are the same as those in Example 1, except that the parameter conditions involved in the preparation process are different (see Table 1 for details):

[0062] In the process of carbonization and cracking in step (1), the heat treatment temperature is 900°C and the heat treatment time is 3 hours.

[0063] Comparative Example 1

[0064] Compared with Example 1, the difference between this comparative example is that the MOF material is not doped and modified in this comparative example, and the mass ratio of the MOF material to the nitrogen source is 1:0 (see Table 2 for details);

[0065] In this comparative example, MOF material is directly used as a precursor after heat treatment, and chemical vapor deposition is performed twice to obtain a MOF-derived screening type carbon sodium negative electrode material. The preparation steps are as follows:

[0066] (1) directly immersing ZIF-8 in deionized water and stirring, stirring for 12 hours and then drying to obtain a mixed solid; placing the mixed solid in a tube furnace, introducing argon gas, and heat treating at 800°C to obtain a carbonized cracking product after heat treatment for 3 hours;

[0067] (2) Stirring the carbonized pyrolysis product in excess 5% HCl for 12 h to ensure that the solution has no bubbles and the pH is acidic, and continue to wash with excess deionized water until the pH of the solution is neutral, and then drying to obtain the ZIF-8 material precursor;

[0068] (3) The ZIF-8 material precursor was placed in a chemical vapor deposition device and argon gas was introduced. After the temperature was raised to 750°C, xylene was introduced as a carbon source gas at a ventilation rate of 100 ml / min and the first heat preservation was performed. After 20 minutes of heat preservation, the first chemical vapor deposition was completed;

[0069] (4) After the first chemical vapor deposition, switch the carbon source gas to methane at a ventilation rate of 10 ml / min as the carbon source gas, and perform a second heat preservation for 4 hours to complete the second chemical vapor deposition;

[0070] (5) After completing two chemical vapor deposition phases, the carbon source gas was turned off, the argon gas was kept flowing, and the temperature was cooled to room temperature at a cooling rate of 10°C / min to obtain a MOF-derived screening-type carbon sodium negative electrode material.

[0071] Comparative Example 2

[0072] The difference between this comparative example and Example 1 is that in this comparative example, an excess amount of nitrogen source is added to nitrogen-dope the MOF material, and the mass ratio of the MOF material to the nitrogen source is 1:3 (see Table 2 for details).

[0073] Comparative Example 3

[0074] The difference between this comparative example and implementation 1 is that in the two vapor deposition processes of this comparative example, the carbon source gas used is methane (see Table 2 for details).

[0075] Comparative Example 4

[0076] The difference between this comparative example and implementation 1 is that in this comparative example, during the two vapor deposition processes, the carbon source gas is not switched, and the carbon source gas used is xylene (see Table 2 for details).

[0077] Comparative Example 5

[0078] The difference between this comparative example and implementation 1 is that in this comparative example, the carbon source gas used in the first vapor deposition process is methane, and in the second vapor deposition process, the carbon source gas used is xylene (see Table 2 for details).

[0079] Comparative Example 6

[0080] The difference between this comparative example and implementation 1 is that chemical vapor deposition is not performed in this comparative example, and nitrogen-doped MOF-derived porous carbon material is directly used as the negative electrode material (see Table 2 for details).

[0081] Comparative Example 7

[0082] The difference between this comparative example and implementation 1 is that this comparative example only performs a chemical vapor deposition process once (see Table 2 for details).

[0083] Comparative Example 8

[0084] The difference between this comparative example and Example 1 is that the CVD precursor used in this comparative example is conventional porous carbon with a specific surface area of ​​1560 m 2 / g, micropores account for 53% of the pore volume.

[0085] Table 1 Preparation parameter conditions of the embodiment

[0086]

[0087] Table 2 Preparation parameter conditions of comparative examples

[0088]

[0089] Test Example 1 Test of MOF-derived porous carbon material precursor before CVD treatment

[0090] Before the CVD treatment, the MOF-derived porous carbon material precursors obtained in the above-mentioned embodiment and comparative example were subjected to N2 adsorption and desorption tests, and the results are shown in Table 3.

[0091] Table 3 Performance test table of MOF-derived porous carbon material precursors

[0092]

[0093] Result analysis:

[0094] It can be seen from Table 3 that the specific surface area of ​​the unheat-treated MOF material (ZIF-8) is 1291 m 2 / g, micropores account for 83.4%, the average pore size ranges from 0.3 to 1.1 nm, and the total pore volume is 0.553 cm 3 / g.

[0095] After the heat treatment of the embodiment and the comparative example, the specific surface area and pore size distribution of the obtained MOF-derived porous carbon material changed. Figure 3 and Figure 6 As shown, in Example 1, when the heat treatment is carried out, the nitrogen source is introduced at a ratio of 1:1.3 for N doping modification, and the surface area of ​​the obtained precursor material is 1615m 2 / g, micropores account for 79.6%, the average pore size ranges from 0.8 to 1.6 nm, and the total pore volume is 49.7 cm 3 / g, in comparative example 1, the surface area of ​​the precursor material obtained after direct heat treatment with ZIF-8 material was 478m 2 / g, micropores account for 5%, the average pore size ranges from 5 to 10 nm, and the total pore volume is 0.205 cm 3 / g.

[0096] In comparative example 2, during heat treatment, a nitrogen source was introduced at a ratio of 1:3 for N-doping modification, and the surface area of ​​the obtained precursor material was 1045 m 2 / g, micropores account for 34%, the average pore size ranges from 1-2 nm, and the total pore volume is 0.341 cm 3 / g.

[0097] From the results of Example 1 and Comparative Example 1, it can be seen that when the MOF material is directly pyrolyzed without modification, the structure is prone to collapse when the pyrolysis temperature is 800°C, so that the pore structure of the MOF material cannot be retained. By doping the material with N elements, the carbon skeleton formed by the evenly dispersed urea during the pyrolysis process protects the structural stability of the MOF material to a great extent. The prepared MOF-derived porous carbon material retains a rich pore structure. Although the pore volume decreases slightly, the specific surface area is greatly increased, and the proportion of micropores is increased. The large specific surface area can ensure a high sodium storage capacity, and the rich microporous structure and N element doping contribute to the reversible formation of sodium clusters in the platform segment, which helps to improve the low-temperature performance of the negative electrode material.

[0098] However, it can be seen from the results of Example 1 and Comparative Example 2 that the amount of nitrogen source added for N-modification must be within a reasonable range to produce excellent results. If an excessive amount of nitrogen source is introduced, it will also lead to a decrease in the specific surface area and the proportion of micropores, affecting the final performance.

[0099] The heat treatment temperature of Example 5 is 900°C, and the surface area of ​​the obtained precursor material is 756m 2 / g, micropores account for 19.5%, the average pore size ranges from 1.5 to 2.3 nm, and the total pore volume is 0.294 cm 3 / g, indicating that even after N-doping modification, an appropriate treatment temperature should be selected. However, if the treatment temperature is too high, the structure of the MOF material will collapse during the pyrolysis process, affecting the stability of the structure. The pore structure cannot be retained, affecting the specific surface area and pore size distribution of the material, resulting in a decrease in the low-temperature performance of the negative electrode material.

[0100] The results of Examples 2-4 and Comparative Examples 3-8 are the same as those of Example 1, indicating that heat treatment within a reasonable range of conditions can also retain a rich pore structure and micropore ratio.

[0101] Test Example 2 Test of MOF-derived Sieving-type Carbon-sodium Anode Material after CVD Treatment

[0102] The MOF-derived porous carbon material precursors obtained after CVD treatment in the above-mentioned embodiments and comparative examples were subjected to N2 adsorption and desorption tests, and the results are shown in Table 3.

[0103] The MOF-derived sieving-type carbon-sodium negative electrode materials obtained in the embodiment and the comparative example were respectively prepared into sodium ion button batteries, and the preparation process was as follows:

[0104] (1) Preparation of negative electrode:

[0105] Step 1, preparation of PVDF (1:10) colloid: PVDF powder was prepared into PVDF colloid using NMP solvent in a planetary mixer, and stirred at 3000 rpm for 6 h until the colloid was clear and transparent without bubbles.

[0106] Step 2: Mix the MOF-derived screening carbon material, PVDF glue, conductive agent SP, and NMP solution in a ratio of 8:1:1, stir at 3000 rpm for 4 hours, and test the slurry viscosity to maintain it at 5000-7000 mPa•s.

[0107] If the viscosity is higher than this range, add more NMP solution to adjust the viscosity, continue stirring for 2 hours, and then continue to measure the viscosity until it meets the requirements.

[0108] Step 3: After passing through a 150-mesh sieve, the product slurry is obtained.

[0109] The method of preparing a carbon negative electrode sheet using the product slurry comprises the following steps:

[0110] The product slurry is coated on a copper foil current collector and placed in a vacuum oven for drying at 100° C. for 12 hours to obtain a dried electrode sheet, which is then cut into round sheets matching button cells to obtain a carbon negative electrode sheet.

[0111] (2) Preparation of sodium ion button battery:

[0112] The invention comprises the sodium ion battery carbon negative electrode, a sodium metal sheet, an electrolyte and a diaphragm; wherein the electrolyte is NaClO4 (EC / DEC 1:1) and the diaphragm is GF / A.

[0113] The sodium ion button cells prepared with the negative electrode materials of the embodiment and the comparative example were respectively used for performance tests at room temperature 25°C, and constant current charge and discharge experiments were carried out at 25°C in the LAND battery test system, with a voltage range of 0V-2.5V and a current density of 50mA / g. The test results are shown in Table 4:

[0114] Table 4 Performance test results of MOF-derived screening type carbon sodium negative electrode materials

[0115]

[0116] Result analysis:

[0117] From the results in Table 4, it can be seen that the MOF-derived screening-type carbon sodium negative electrode material obtained by the preparation method described in Example 1 of the present invention has the best comprehensive performance, such as Figure 2 As shown in Figure 2, the specific surface area of ​​the precursor before CVD treatment can reach up to 1615m 2 / g, and the specific surface area of ​​the material after CVD treatment is 5.5 m 2 / g, and the material was prepared into negative electrode for sodium ion button battery test. The results are as follows Figure 1 As shown in the first cycle charge and discharge curve of the sodium ion battery negative electrode material, the first cycle reversible capacity is 419 mAh / g and the first coulombic efficiency is 89%, which is the optimal embodiment of the present invention.

[0118] The MOF material of comparative example 1 was not modified by N doping, and the pore structure could not be retained. The specific surface area and micropore ratio of the obtained material were significantly smaller. It was directly used as a precursor for two chemical vapor depositions. The obtained MOF-derived screening-type carbon sodium negative electrode material was prepared into a negative electrode for sodium ion button battery testing. The first cycle reversible capacity was 246 mAh / g, and the first coulombic efficiency was 76%. Compared with the embodiment, the performance was significantly reduced. Figure 4 and Figure 5 shown.

[0119] The MOF material of Example 2 was modified by N doping. When the N doping was excessive, the specific surface area and micropore ratio of the obtained material decreased slightly, which eventually led to a decrease in performance. The first-cycle reversible capacity dropped to 368 mAh / g, and the first coulombic efficiency dropped to 82%.

[0120] It can be seen that the preparation process of the precursor will affect the performance of the final negative electrode material.

[0121] At the same time, the materials obtained from Comparative Examples 3 to 8 were prepared into negative electrodes for sodium ion button battery testing. Compared with the results obtained in Example 1, the first-cycle reversible capacity and the first coulombic efficiency of Comparative Examples 3-7 decreased, which reduced the frequency doubling performance and cycle stability of the battery negative electrode, and the overall performance of the battery was poor; the first-cycle reversible capacity and the first coulombic efficiency of Comparative Example 8 were not much different, and compared with Example 1, the precursor selection of Comparative Example 8 was different from that of Comparative Examples 3 to 8; while the precursors of Comparative Examples 3-7 were the same, and the test results of the precursors obtained in Test Example 1 showed that the performance of the precursors was also the same, except that the chemical vapor deposition process was different. Among them, Comparative Example 6 did not perform a chemical vapor deposition process, and the MOF-derived porous carbon material obtained by N-doped modification was directly used as a negative electrode material for sodium ion button battery testing. The results showed that although it had a rich closed-pore structure, the pores could not be adjusted, resulting in poor battery performance, and the first-cycle reversible capacity and the first coulombic efficiency were significantly low. While in Comparative Example 7, only the first step of chemical vapor deposition using xylene as the carbon source gas is performed. Although it still exhibits a certain specific surface area, it also leads to a significant decrease in the first-cycle reversible capacity and the first coulombic efficiency of the material.

[0122] It can be seen that it is also very important to carry out two chemical vapor deposition processes. If chemical vapor deposition is not carried out or only one chemical vapor deposition is carried out, the pore structure of the obtained material will not change, and the deposition at the shrinkage entrance will not enter the pore belly, and the result of adjustable pore size cannot be achieved.

[0123] Comparative Examples 3-5 all performed chemical vapor deposition twice, but the parameter conditions for chemical vapor deposition were different, resulting in different results. Compared with Examples 1-4, the first-cycle reversible capacity and the first coulombic efficiency decreased. This result shows that even if chemical vapor deposition is performed twice, it is very important to strictly control the vapor deposition process. The type of carbon source gas and the corresponding addition order, ventilation rate and insulation time will affect the final performance of the negative electrode material.

[0124] Test Example 3 Low temperature performance test

[0125] The sodium ion button batteries prepared with the negative electrode materials of Example 1, Comparative Example 1 and Comparative Example 8 were respectively used for low-temperature performance testing: the button batteries were placed in a constant temperature cabinet at -30°C and connected to an external LAND battery testing system to conduct a -30°C constant current charge and discharge experiment with a voltage range of 0V-2.5V and a current density of 50mA / g.

[0126] The results are as follows Figure 7 As shown, it can be seen that compared with Example 1, although Comparative Example 8 can also maintain good first-cycle capacity and first coulomb efficiency at room temperature, the performance difference at low temperature is relatively large. Among them, Example 1 adopts the method of the present application to obtain the negative electrode material, the micropore ratio is 79.6%, and the capacity retention rate at -30°C is 75%, which can show good low-temperature performance, while Comparative Example 8 uses the disclosed conventional porous carbon for chemical vapor deposition to obtain a carbon negative electrode material, the micropore ratio is 46.1%, the capacity retention rate at -30°C is only 50%, and the stability is poor, showing poor low-temperature performance. In addition, the micropore ratio of Comparative Example 1 is as low as 5%, which is close to complete loss of capacity, and the low-temperature performance is the worst, and it cannot be used normally. A comprehensive comparison of Example 1, Comparative Examples 1 and 8 shows that the micropore ratio significantly affects the low-temperature performance of the material. The higher the micropore ratio of the vapor deposition precursor, the better its low-temperature performance.

[0127] In summary, the MOF-derived screening-type carbon-sodium negative electrode material obtained by the preparation method of the present invention can have both rich closed-pore structure and adjustable micropore diameter, improve the initial coulombic efficiency and sodium storage capacity, and significantly improve the low-temperature performance of the negative electrode material. The excellent effect produced by the present invention is obtained by preparing a MOF-derived porous carbon material precursor by N-doping and heat-treating the MOF material, and then performing a unique two-step chemical vapor deposition process. Only the material obtained under the synergistic effect of the N-doping mass ratio, heat treatment temperature, carbon source gas type and chemical vapor deposition temperature within a certain range has the excellent performance of the present application.

[0128] For those skilled in the art, the invention is not limited to the details of the above exemplary embodiments, and can be implemented in other specific forms without departing from the spirit or basic characteristics of the invention; therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the invention is limited by the appended claims rather than the above description, so it is intended to include all changes that fall within the meaning and scope of the equivalent elements of the claims. Any reference numerals in the claims should not be regarded as limiting the claims involved.

[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any minor modifications, equivalent substitutions and improvements made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a MOF-derived screening-type carbon sodium negative electrode material, comprising the preparation of a MOF-derived porous carbon material precursor and the preparation of a screening-type carbon negative electrode material, characterized in that: The MOF-derived porous carbon material precursor is prepared by modifying a MOF material and a nitrogen source through heat treatment, wherein the doping mass ratio of the MOF material to the nitrogen source is 1:0.3-1:2, and the heat treatment temperature is 600-800°C; The screening type carbon negative electrode material is prepared by a porous carbon material precursor derived from MOF through two chemical vapor deposition processes at the same deposition temperature and different carbon source gases, wherein the deposition temperature of the chemical vapor deposition process is 700-900°C; The carbon source gas includes aromatic hydrocarbon vapor and C1-C3 hydrocarbons, the aromatic hydrocarbon vapor is the carbon source gas in the first chemical vapor deposition process, and the ventilation rate is 5-300mL / min; the aromatic hydrocarbon vapor is benzene, toluene or xylene; the C1-C3 hydrocarbons are the carbon source gas in the second chemical vapor deposition process, and the ventilation rate is ≥10mL / min; the C1-C3 hydrocarbons are methane, ethane, acetylene or propane.

2. The method for preparing the MOF-derived screening-type carbon sodium negative electrode material according to claim 1, characterized in that: The MOF material is ZIF-8, ZIF-5 or ZIF-7; the nitrogen source is urea, melamine, glutamine, pyridine or pyrrole.

3. The method for preparing the MOF-derived screening-type carbon sodium negative electrode material according to claim 1, characterized in that: The following steps are involved: (1) Soaking the MOF material and the nitrogen source in deionized water or anhydrous ethanol in proportion and stirring, stirring for 12 hours and then drying to obtain a mixed solid; placing the mixed solid in a tubular furnace, passing a protective gas, and performing heat treatment to obtain a carbonized cracking product after heat treatment for 2-4 hours; (2) Add 5% HCl to the carbonized pyrolysis product and stir for 12 h until the solution has no bubbles and the pH is acidic, continue to wash with deionized water until the pH of the solution is neutral, and then dry it to obtain a MOF-derived porous carbon material precursor; (3) placing the MOF-derived porous carbon material precursor in a chemical vapor deposition device for chemical vapor deposition, first introducing a protective gas, heating to the deposition temperature, introducing aromatic hydrocarbon vapor, and performing the first heat preservation. After the heat preservation lasts for 10-30 minutes, the first chemical vapor deposition is completed; (4) After the first chemical vapor deposition is completed, switch the carbon source gas, introduce C1-C3 hydrocarbons, and perform a second heat preservation, the heat preservation time is ≥3h, and the second chemical vapor deposition is completed; (5) After completing two chemical vapor deposition phases, the carbon source gas is turned off, the protective gas is kept flowing, and the temperature is cooled to room temperature at a cooling rate of 2-10°C / min to obtain a MOF-derived screening-type carbon sodium negative electrode material.

4. The method for preparing the MOF-derived screening-type carbon sodium negative electrode material according to claim 3, characterized in that: The protective gas described in steps (1) to (5) is nitrogen or argon.

5. The method for preparing the MOF-derived screening-type carbon sodium negative electrode material according to claim 3, characterized in that: The specific surface area of ​​the MOF-derived porous carbon material precursor obtained in step (2) is 1300-1700 m 2 / g, the average pore size range is 0.5-2.1nm, and the total pore volume is 0.46-0.5cm 3 / g, and micropores account for 70-80%.

6. A MOF-derived screening-type carbon sodium negative electrode material, characterized in that: The preparation method is described in any one of claims 1 to 5.

7. Use of the MOF-derived sieving-type carbon-sodium negative electrode material according to claim 6 in a sodium ion battery.

Citation Information

Patent Citations

  • Preparation method of non-noble metal nitrogen-doped porous carbon electrocatalyst

    CN108067278A

  • MOF-5 derived porous carbon-based nano material and preparation method thereof

    CN113113614A